Association of high-sensitivity troponin T and I with the severity of stable coronary artery disease in patients with chronic kidney disease. (November 2020) - Brunner, Fabian J.; Kröger, Friederike; Blaum, Christopher; Goßling, Alina; Lorenz, Thiess; van Erckelens, Elisabeth; Brätz, Julian; Westermann, Dirk; Blankenberg, Stefan; Zeller, Tanja; Waldeyer, Christoph; Seiffert, Moritz
Abstract: Background and aims: Cardiac troponin blood levels are frequently elevated in patients with impaired renal function. Their predictive value for the severity of stable coronary artery disease (CAD) remains unclear in these cases. Therefore, we aimed to evaluate the blood levels of high-sensitivity troponin T and I (hsTnT/I) and their association with the severity of stable CAD in patients with chronic kidney disease. Methods: Overall, 2209 patients with suspected stable CAD undergoing invasive coronary angiography were included in an ongoing prospective cohort study. We identified 595 patients with impaired renal function defined as an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73 m 2 . Coronary morphology was assessed by the number of affected major coronary vessels (CAD classification), SYNTAX, and Gensini scores. hsTnT/I blood levels were measured by three latest-generation assays (Roche Diagnostics Elecsys, Abbott ARCHITECT STAT, and Singulex Clarity). Ordinal logistic regression for the severity of CAD adjusted by classical cardiovascular risk factors and eGFR were performed with each troponin assay as an independent variable. Results: Mean age was 72.9 ± 9.8 years (33.6% female). Median eGFR was 47.5 ml/min/1.73 m 2 (interquartile range [IQR] 34.9, 54.1). For the association of Roche-hsTnT, Abbott-hsTnI, and Singulex-hsTnI with the CAD classification, odds ratios per standard deviation (OR) were 1.27 (95% confidence interval [CI] 1.07–1.51), 1.21 (CI 1.02–1.44), and 1.24 (CI 1.04–1.47), respectively. The associations for the investigated assays with SYNTAX and Gensini scores, respectively, were OR 1.40, CI 1.11–1.78 and OR 1.24, CI 1.01–1.51 (Roche-hsTnT), OR 1.42, CI 1.12–1.78 and OR 1.25, CI 1.02–1.52 (Abbott-hsTnI), OR 1.38, CI 1.09–1.74 and OR 1.25, CI 1.02–1.53 (Singulex-hsTnI). Conclusions: In patients with impaired renal function, blood levels of hsTnT/I were significantly associated with the severity of stable CAD. These findings may help clinicians guide further diagnostic assessment. Graphical abstract: Image 1 Highlights: High-sensitivity troponins (hsTn) are elevated in patients with chronic kidney disease (CKD). The association of elevated hsTn with coronary artery disease (CAD) remains unclear in CKD. The present study demonstrates higher hsTn blood levels in patients with CAD. hsTn are associated with the severity of CAD even after adjustment for CV risk factors and eGFR.